2022
DOI: 10.1002/pul2.12090
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world treatment patterns, healthcare resource utilization, and cost among adults with pulmonary arterial hypertension in the United States

Abstract: Treatment for pulmonary arterial hypertension (PAH) has evolved over the past decade, including approval of new medications and growing evidence to support earlier use of combination therapy. Despite these changes, few studies have assessed real-world treatment patterns, healthcare resource utilization (HCRU), and costs among people with PAH using recent data. We conducted a retrospective cohort study using administrative claims from the HealthCore Integrated Research Data-base®. Adult members with claims for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…As for treatment preferences, our participants mostly preferred monotherapy (82.8%) for patients with mild/moderate PAH diagnosed with a negative vasoreactivity test, and ERAs were the most preferred in this group. Similarly, in real-world data involving newly diagnosed USA patients with PAH, nearly 94% of patients commenced treatment with monotherapy and the most common treatment preference were PDE-5 inhibitors (70.0% of patients) [21]. Preston et al found in their study that a significant proportion of patients were treated with PDE-5 inhibitors in Argentina and the USA, whereas in Europe, an equal proportion of patients were treated with PDE-5 inhibitors and ERAs [13].…”
Section: Discussionmentioning
confidence: 94%
“…As for treatment preferences, our participants mostly preferred monotherapy (82.8%) for patients with mild/moderate PAH diagnosed with a negative vasoreactivity test, and ERAs were the most preferred in this group. Similarly, in real-world data involving newly diagnosed USA patients with PAH, nearly 94% of patients commenced treatment with monotherapy and the most common treatment preference were PDE-5 inhibitors (70.0% of patients) [21]. Preston et al found in their study that a significant proportion of patients were treated with PDE-5 inhibitors in Argentina and the USA, whereas in Europe, an equal proportion of patients were treated with PDE-5 inhibitors and ERAs [13].…”
Section: Discussionmentioning
confidence: 94%
“…That a debilitating disease like PAH have high HCRU after diagnosis is neither surprising nor unknown, 9 , 10 , 11 , 12 , 15 , 16 , 17 however, the costs for society before diagnosis is less studied 10 , 17 , 31 , 32 and the magnitude of productivity loss has not been shown before. Hospitalizations as a substantial cost driver after the PAH diagnosis 10 , 11 , 15 , 16 , 17 was confirmed by the present study and, importantly, productivity loss was found to be equally costly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown diverging results of the main post‐diagnosis cost driver as being either related to drug costs 10,31,32 or to nondrug related healthcare costs 14–16 . This discrepancy might relate to that a majority of the previous studies are based on patients identified from insurance claim databases or databases using criteria such as treatment, procedures, hospitalization, and/or ICD‐codes and often include both prevalent and incident patients 10,11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…As such, this study provides important context to the findings of previous studies on the economic burden of PAH overall. Prior evidence indicates that diagnosed PAH is associated with a substantial economic burden in the US [ 17 21 ]. In a retrospective administrative claims-based study of patients with diagnosed PAH in the US from 2015 to 2020, mean total all-cause health care costs after PAH treatment initiation (mean follow-up of 1.5 years) were US$14,201 PPPM [ 21 ], which is consistent with the mean total all-cause health care costs obtained in our overall sample (US$14,129 PPPM).…”
Section: Discussionmentioning
confidence: 99%
“…Prior evidence indicates that diagnosed PAH is associated with a substantial economic burden in the US [ 17 21 ]. In a retrospective administrative claims-based study of patients with diagnosed PAH in the US from 2015 to 2020, mean total all-cause health care costs after PAH treatment initiation (mean follow-up of 1.5 years) were US$14,201 PPPM [ 21 ], which is consistent with the mean total all-cause health care costs obtained in our overall sample (US$14,129 PPPM). Previous studies further suggest that hospitalizations are the main driver of the substantial HRU and cost burden among patients with PAH [ 6 , 18 , 20 , 22 – 28 ].…”
Section: Discussionmentioning
confidence: 99%